2014
DOI: 10.1590/s0100-204x2014000700006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of grape juices from different cultivar and rootstock combinations

Abstract: -The objective of this work was to evaluate the influence of different combinations of grape cultivars and rootstocks on chemical characteristics of grape juices. Six treatments were evaluated, consisting of combinations between the Isabel Precoce and BRS Cora grape cultivars and the 'IAC 766', 'IAC 313', and 'IAC 572' rootstocks. Approximately 10 L of juice were obtained per treatment. Analyses of color, total soluble solids content, pH, anthocyanins, total phenolics, total sugars, and quantification and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Lamine et al [ 56 ] used the PCA method to discriminate Tunisian grape cultivars and reported high morphological diversity. Nassur et al [ 57 ] used the PCA method on grape cultivars in Brazil, and based on principal component analysis (PCA), all grape cultivars were discriminated and high morphological variation was observed among the accessions. Istrate et al [ 58 ] used applications of the principal component analysis (PCA) at grape varieties from the serogroup Coarnă neagră for establishing phenotypical variability and found great diversity among cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Lamine et al [ 56 ] used the PCA method to discriminate Tunisian grape cultivars and reported high morphological diversity. Nassur et al [ 57 ] used the PCA method on grape cultivars in Brazil, and based on principal component analysis (PCA), all grape cultivars were discriminated and high morphological variation was observed among the accessions. Istrate et al [ 58 ] used applications of the principal component analysis (PCA) at grape varieties from the serogroup Coarnă neagră for establishing phenotypical variability and found great diversity among cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found by Lima et al (2014) who evaluated juices of the VIO and IP cultivars in the São Francisco Valley and found higher contentes of anthocyanins in VIO juices (464.00 mg L -1 ) and lower values in IP (29.00 mg L -1 ). Nassur, Pereira, Alves and Lima (2014) evaluated juices from the COR and IP cultivars on different rootstocks in Petrolina-PE and found values from 22.80 mg L -1 to 168.00 mg L -1 for COR and 35.12 mg L -1 at 43.53 mg L -1 for PI.…”
Section: Resultsmentioning
confidence: 99%
“…The changes on plant physiology that could interfere on secondary metabolism composition leading to a higher phenolic composition of the wines should be better investigated. Nassur et al (2014) observed that the grape cultivar can influence -Moreno et al, 2003).…”
Section: Resultsmentioning
confidence: 99%